Knowledge production in education: Post-structuralism as epistemological potency (Práxis Educativa, 2017)
This paper aims to analyze the epistemological and methodological potentialities of Post-structuralism in education research. With a theoretical-bibliographic character, the research takes as main references Michel Foucault, Gilles Deleuze and Jacques Derrida’s contributions in order to problematize the modern metanarratives and the processes of knowledge production in this area. By problematizing modern metanarratives and pointing out the historical, contextual character, inherent in the process of knowledge production, this epistemological perspective has triggered a number of concerns, doubts and discontinuities that have reverberated in investigative processes in that area. Being open to this epistemological field may both contribute to the deconstruction of the conceptual apparatus of modernity, which has strongly marked the education research, and bring other epistemological and methodological possibilities for knowledge production in that area. In this sense, the potentiality of this epistemological and methodological perspective for research in education is the multiplicity of possibilities that it provides.  Keywords: Research. Education. Post-structuralism.